معوقات الأداء الإبداعي لدى مدرسي العلوم في المرحلة المتوسطة من وجهة نظرهم - منصور، رشا عبدالهادي صالح (جامعة الكوفة - كلية التربية للبنات, 2021)
هدف البحث الحالي للتعرف على معوقات الأداء الإبداعي لدى مدرسين العلوم في مرحلة المتوسطة من وجهة نظرهم، ولتحقيق هدف البحث استخدمت الباحثة المنهج الوصفي، وتكون مجتمع البحث من مدرسي المدارس المتوسطة في مديرية تربية النجف الإشراف للعام الدراسي (2018-2019)، وتكونت عينة البحث من (101) من مدرسي العلوم وقد اختيرت العينة بطريقة عشوائية من مجتمع البحث. واعدت الباحثة (استبانة) تشمل أربعة محاور تتضمن معوقات تتعلق بالمدرس، والطالب، والإدارة المدرسية، والمنهج الدراسي، وبعد عرض الاستبانة على الخبراء والمحكمين للتأكد من الخصائص السايكومترية أصبحت بصيغتها النهائية مكون من (30) فقرة، وتم التحقق من صدقها وثباتها، وبلغت قيمة معامل الثبات ألفا كرونباخ (0.83)، قد استخدمت الباحثة مجموعة من الوسائل الإحصائية، كما أظهرت النتائج البحث وجود فروق ذات دلالة إحصائية بين أفراد عينة البحث تعزى للمتغير الجنس ولصالح الإناث، وكذلك عدم وجود فروق ذات دلالة إحصائية تعزى للمتغير (المؤهل العلمي، وسنوات الخبرة)، وقد وضعت الباحثة عدد من التوصيات والمقترحات المتعلقة بنتائج البحث. The aim of the current research is to identify the obstacles to the creative performance of science teachers in the middle stage from their point of view, and to achieve the research goal, the researcher used the descriptive approach, and the research community consisted of middle school teachers in the Najaf Education Directorate for the academic year (2018-2019) The research sample consisted of (101) teachers, and the sample was randomly selected from the research community. The researcher prepared a (questionnaire) that includes four axes that include obstacles related to the teacher, the student, the school administration, and the curriculum. And after the questionnaire was presented to experts and arbitrators to verify the psychometric properties, it became in its final form consisting of (30) paragraphs, and their validity and reliability were verified, and the value of the reliability coefficient Cronbach Alpha (0.83) The researcher used a set of statistical methods, and the results of the research showed that there are statistically significant differences between the members of the research sample due to the variable gender and in favor of females, as well as the absence of statistically significant differences attributable to the variable (academic qualification, years of experience), and the researcher developed a number of recommendations And proposals related to the research results.
Keywords: التعليم الإبداعي -- الإبداع المنتج -- الإبداع التعبيري -- الإبداع الإبتكاري -- التعليم المتوسط